2022
DOI: 10.1002/adpr.202200190
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinarily Transparent Metaldielectrics for Infrared and Terahertz Applications

Abstract: Metamaterials are extremely important in advanced technologies, but usually, they rely on the resonant behavior of their constituent blocks. This strongly limits the application of metamaterials to particular frequency band ranges. However, metamaterials with broadband behaviors are highly desirable and are essential for many applications. Herein, recently discovered metamaterials that are composed of densely packed metallic nanoparticles but behave as effective dielectrics are explored. Such metamaterials are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…[ 1 ] In this way, we solve for the effective index of compact metallic structures with high accuracy, using finite‐differences or finite‐elements to discretize our system. Interestingly, when the particles are much smaller than the wavelength, even in the case of small gaps (when multipolar orders are expected), the following simple Maxwell‐Garnett approximation gives accurate results: [ 2 ] εeffbadbreak=εm2ρ(εiεm)+εi+2εm2εm+εiρ(εiεm)$$\begin{equation} \epsilon _{eff} = \epsilon _{m}\frac{2\rho (\epsilon _i-\epsilon _m) + \epsilon _i + 2\epsilon _m}{2\epsilon _m+\epsilon _i-\rho (\epsilon _i-\epsilon _m)} \end{equation}$$where, ϵ eff is the effective dielectric constant of the medium, ϵ i of the inclusions, and ϵ m of the matrix; and ρ is the volume fraction of the inclusions. The above expression considers spherical inclusions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] In this way, we solve for the effective index of compact metallic structures with high accuracy, using finite‐differences or finite‐elements to discretize our system. Interestingly, when the particles are much smaller than the wavelength, even in the case of small gaps (when multipolar orders are expected), the following simple Maxwell‐Garnett approximation gives accurate results: [ 2 ] εeffbadbreak=εm2ρ(εiεm)+εi+2εm2εm+εiρ(εiεm)$$\begin{equation} \epsilon _{eff} = \epsilon _{m}\frac{2\rho (\epsilon _i-\epsilon _m) + \epsilon _i + 2\epsilon _m}{2\epsilon _m+\epsilon _i-\rho (\epsilon _i-\epsilon _m)} \end{equation}$$where, ϵ eff is the effective dielectric constant of the medium, ϵ i of the inclusions, and ϵ m of the matrix; and ρ is the volume fraction of the inclusions. The above expression considers spherical inclusions.…”
Section: Resultsmentioning
confidence: 99%
“…However, it can be shown that we can obtain analytical expressions for the effective refractive index when metal nanoparticles have simple shapes such as cubes, cylinders, etc. [ 2 ]…”
Section: Resultsmentioning
confidence: 99%
“…Nanofocusing has emerged as a powerful tool in the field of nanophotonics, offering unprecedented control and manipulation of light at the nanoscale. The technique enables the concentration of optical energy to dimensions well below the diffraction limit of light holding great promise for a wide range of applications, including data communications, high-resolution imaging, optical sensing, and nanoscale spectroscopy . Nanofocusing is best recognized in nanophotonic waveguides that exhibit adiabatic tapering using either sharp metallic tips ,, or narrow gaps in metal or dielectric , structures. Here, we explore nanofocusing in resonant optical antennas.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, metallic nanoparticles and the nanogaps in particle clusters have been utilized to enhance the weak ROA signal from chiral molecules absorbed on the surface of those particles or in the gaps, where electric field hot spots exist. , The majority of researchers have focused on studying the polarization difference in the intensity of Raman scattering from chiral molecules on isotropic surfaces, with the common understanding being that the ROA signal arises from the intrinsic properties of the Raman tensor of the analyte (the chirality of molecules). However, it is also crucial to consider the orientation of the molecule with respect to the metallic nanoparticle surfaces and the chiral properties of the nanoparticles, as these can also influence the Raman signal.…”
mentioning
confidence: 99%